Clinical and laboratory characteristics of solitary rectal ulcer syndrome: a retrospective analysis of 36 case - Furkan Ali Uygur; Muhammed Emin Göktepe; Gökhan Aydın; Enes Ağırman; Ahmet Cumhur Dülger (Scientific Reports)
Abstract The primary objective of this study was to evaluate the clinical, laboratory, and histological characteristics of solitary rectal ulcer syndrome (SRUS) and assess the outcomes associated with various management strategies. This retrospective observational study was conducted at Giresun Education and Research Hospital. This study included patients diagnosed with SRUS between January 2020 and January 2024. Demographic information, clinical presentation, primary diagnosis, and laboratory parameters were obtained from electronic medical records. Statistical analysis was performed using SPSS software, and the chi-square test was used to compare categorical variables. A total of 36 patients diagnosed with SRUS were included, with the majority being male (80.6%), and the mean age of participants was 75.6 years. Hematochezia was identified as the most common initial symptom (61.1%), followed by abdominal pain (16.7%) and constipation (11.1%). Laboratory findings revealed significant abnormalities, including mean hemoglobin levels of 10.0 ± 2.4 g/dL and mean CRP levels of 56.7 ± 65.4 mg/L. Histopathological analysis showed that 38.9% of patients had normal biopsy results, whereas inflammation and dysplasia were observed in 41.7% and 2.8% of cases, respectively. Additionally, a statistically significant difference in age was observed between the patients presenting with different initial symptoms (p = 0.028). The study also found that biopsy results varied significantly across symptom groups (p = 0.012), and although differences in hemoglobin and hematocrit levels across biopsy groups were noted, they were not statistically significant. This study offers a comprehensive analysis of SRUS, emphasizing the importance of detailed clinical and laboratory evaluation. Hematochezia emerged as the most prevalent symptom, and ulcerative colitis was identified as the primary diagnosis. Significant associations were observed between various clinical parameters and patient outcomes, highlighting the necessity of a multidisciplinary approach in managing SRUS.